Kumpulan Indeks Beranotasi Judul Disertasi (S3) Bidang Pendidikan Periode 2008-2012 di Perpustakaan Pascasarjana Universitas Negeri Padang - Irman, Irsyadi; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of writing this paper is to describe the process of collecting dissertation titles index (S3) annotated education period 2008-2012 at Padang State University Graduate Library. Datawere collected through observation and direct participation by collecting data directly from the original source. Analyzing data is done by descriptive. By analyzing the data, it was concluded that: the making of the title index is conducted on a dissertation that subjek education. Dissertation indexed taken from years 2008-2012, amounting to 29 titles. The process of creating an annotated index dissertation title starts with searching for information on a dissertation that will be indexed, selecting and classifying dissertation, recording data, making annotations, specify keywords, create indexes dissertations, and typed index. Dissertation titles index arranged alphabetically title, author index, and is equipped with a keyword index.